Pengaruh Faktor Eksternal Terhadap Nilai Perusahaan (PBV) dan Harga Saham Terhadap Perusahaan Manufaktur di Bursa Efek Indonesia - Suryantini, Ni Putu Santi; Arsawan, I Wayan Edi (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2015)
The  aims  of this research  i s  to examine  the  influence  of    external  factors on  f irm  value,   the effect  of   company value  on stock  price,  and influence  of  external factors  on  stock  price. The  samples  were 30  manufacturing companies  li sted  in  Indonesia  Stock  Exchange  through  pusposive  sampling.  This  study  applied  secondary data  based  on  documentation  of the  companies.   Data  analysis  was performed  by  using  Smart  PLS.  Out  of the three indicators of external factors, two of them i.e.  inflation and exchange rate,  met  the criterion,  because they have loading factor above 0,5 .  The resul ts  show that, external factors negatively effect firm value with coefficient  value  of  0.0933,  means  that  i f  external   factors  changes,  company’ s  value  thr ough  PBV ,  move towar d  negative  di r ection.  V alue  of  company  influence  stock  price  positively  with  coeff icient  value  of   0.0637. Additionally,  external   factors  show  negat ive  effect   on  stock  price  with  coefficient  value  of  0.1019,  as  an indication that the  changes of  external factor  has negative  impl ication to  the  stock price
Keywords: external factors , f irm value and stock price.